Excessive Sodium Intake Leads to Cardiovascular Disease by Promoting Sex-Specific Dysfunction of Murine Heart - Chen, Xiuli; Wu, Haiying; Huang, Shenzhen (Frontiers in Nutrition, 2022)
Background: Globally, high-salt diet (HSD) has become a threat to human health as it can lead to a high risk of cardiac damage. Although some studies investigating HSD have been carried out, the majority have been conducted in males, and there are few female-specific studies, thereby ignoring any effects of sex-specific damage on the heart. In this study, we determined how HSD induces different pathways of cardiovascular diseases through sex-specific effects on cardiac damage in mice. Methods: An HSD murine model of male and female C57BL/6J mice was fed with sodium-rich chow (4% NaCl). After 8 weeks, cardiac tissues were collected, and the whole gene transcriptome of hearts of male and female mice was characterized and analyzed using high-throughput RNA sequencing. Immunohistochemistry staining was used to further assess the harmful effects of HSD on protein expression of genes associated with immunity, fibrosis, and apoptosis in male and female mice. Results: HSD drastically altered the cardiac transcriptome compared to that of the normal heart in both male and female mice and had a sex-specific effect on the cardiac composition in the transcriptome. HSD produced various differentially expressed genes and affected different KEGG pathways of the transcriptome in male and female mice. Furthermore, we found that HSD induced different pathways of cardiovascular disease in the male mice and female mice. Pathway of hypertrophic cardiomyopathy is significantly enriched in HSD-treated male mice, while pathway of dilated cardiomyopathy is significantly enriched in HSD-treated female mice. Finally, metabolism, immunity, fibrosis, and apoptosis in the mouse heart showed sex-specific changes predicting cardiac damage. Conclusion: Our results demonstrate that HSD adversely impacts cardiac structure and function by affecting the metabolism, immunity, fibrosis, and apoptosis in the murine heart, and induces the mouse to suffer from sex-specific cardiovascular disease. This study provides a new perspective and basis for the differences in the pharmacology and interventional treatment of sex-specific cardiovascular diseases induced by HSD in men and women.